Association between weight gain and knee osteoarthritis: a systematic review. Issue 3 (March 2023) - Solanki, P.; Hussain, S.M.; Abidi, J.; Cheng, J.; Fairley, J.L.; Page, M.J.; Cicuttini, F.M.; Wluka, A.E.
Summary: Objective: Although weight loss is recommended to manage knee osteoarthritis (KOA), adults tend to gain weight with age which may affect KOA symptoms and progression. We conducted a systematic review and data synthesis to investigate the association between weight gain and KOA, defined by clinical features, structural progression, and total knee replacement (TKR). Design: MEDLINE and EMBASE were systematically searched for controlled trials and cohort studies of participants with (or at risk of) KOA examining the relationship between weight gain and KOA clinical features (pain, function, quality of life), structural progression, and TKR. Risk of bias was assessed using the ROBINS-I tool. Results were organised by outcome, with meta-analyses performed where appropriate. Results: Twenty-three studies were included. Results showed significant detrimental effects of weight gain on pain (4 of 7 studies), stiffness (2 of 2 studies), function (5 of 6 studies), and the single studies examining quality of life, and clinical and radiographic KOA. Weight gain adversely affected cartilage (6 of 9 studies), bone marrow lesions (1 of 4 studies), meniscal damage (1 of 3 studies) and effusion/synovitis (1 of 1 study). Weight gain significantly increased TKR (3 of 6 studies): meta-analysis of 2 with available data demonstrated significant increases in TKR/5 kg weight gain in women, HR 1.34 (95% CI 1.18–1.51), and in men, HR 1.25 (95% CI 1.16–1.34). Conclusions: Weight gain in adults is associated with increased clinical and structural KOA and TKR. Prevention of weight gain should be considered to improve outcomes in KOA.